Field reports form for submitting seasonal observations of Iowa birds, Jim Fuller, Spring 1994 - Fuller, James L.et al (1994)
An annotated list of birds sighted by Jim Fuller. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed